Platelets Mitochondrial Function Depends on Coenzyme Q10 Concentration in Human Young, Not in Elderly Subjects - Gvozdjáková, Anna; Sumbalová, Zuzana; Kucharská, Jarmila; Chládeková, Anežka; Rausová, Zuzana; Vancová, Olga; Kubalová, Mária; Kuzmiaková, Zuzana; Nemec, Michal; Ulicná, Olga; Mojto, Viliam (Journal of Nutritional Therapeutics, 2019)
Ageing is characterized by a progressive decline in the physiological functions of various organs. Mitochondrial alterations occurring in senescence. Antioxidants, including coenzyme Q10 concentration, fall with ageing and contribute to enhanced oxidative stress age-related diseases. The impairment of platelet mitochondrial function occurs in a broad spectrum of diseases. The aim of this study was to evaluate mitochondrial function in platelets in elderly and young human controls and correlate it with a concentration of coenzyme Q10. Platelets mitochondrial function was determined by the use of High-Resolution Respirometry method. We did not find significantly decreased platelet mitochondrial function in elderly subjects. Dependence of platelets mitochondrial respiratory chain function and ATP production at Complex I on a concentration of coenzyme Q10 in platelets and whole blood in young not in elderly human volunteers was documented. This dependence was not found for Complex II in any group. Platelet mitochondrial coenzyme Q10 concentration was insufficient for improving platelet mitochondrial function in elderly human subjects. Recommending supplementation with coenzyme Q10 in elderly and aged humans is waranted. High-Resolution Respirometry method offers a perspective to diagnose mitochondrial energy metabolism which might be useful for further studies in patients with mitochondrial disorders. Our results could contribute to the explanation of platelets mitochondrial function in elderly and aged human subjects.